2021
DOI: 10.1080/14760584.2021.1984891
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from a mature acellular pertussis vaccination program and strategies to overcome suboptimal vaccine effectiveness

Abstract: Introduction: Despite high vaccination coverage among children and adolescents, pertussis remains a public health problem, with large outbreaks occurring periodically in the US and other developed countries. Areas covered: We examine lessons learned more than 20 years after implementation of programs which use only acellular pertussis vaccines and propose avenues for possible effective use of acellular pertussis vaccine to prevent large outbreaks. Expert Opinion: Acellular pertussis vaccines were introduced mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…The clinical aspect of the results of this research is how important it is for booster vaccines to be given to children in an effort to maintain antibodies at levels that can provide protection against pertussis because antibody levels will decrease as age increases. [9][10][11][12][13][14] The results of the study showed that there were more subjects in the DPaT vaccine group with antibody titer levels ≥24 IU/mL than in the DPwT vaccine group, although this result was not statistically significant. Only 25% of all samples from both groups had antibody results that were considered to provide protective value.…”
Section: Discussionmentioning
confidence: 79%
“…The clinical aspect of the results of this research is how important it is for booster vaccines to be given to children in an effort to maintain antibodies at levels that can provide protection against pertussis because antibody levels will decrease as age increases. [9][10][11][12][13][14] The results of the study showed that there were more subjects in the DPaT vaccine group with antibody titer levels ≥24 IU/mL than in the DPwT vaccine group, although this result was not statistically significant. Only 25% of all samples from both groups had antibody results that were considered to provide protective value.…”
Section: Discussionmentioning
confidence: 79%